Photoperiod-temperature response - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
Photoperiod screening has continued at CIAT-Palmira throughout 1984 using 18 h daylengths to delay flowering. Materials evaluated included lines from various EP and the germplasm collection and the results from previous screening efforts have been compiled into a list of photoperiod responses of over 3000 materials. However, the strong interaction between photoperiod sensitivity and temp. has complicated attempts to predict optimal photoperiod responses for different bean growing seasons. To clarify this problem, retrospective studies, modeling of IBYAN results, and use of an International Flowering and Adaptation Nursery (IFAN) have been made. (CIAT)